Le pioupiou de France - chanson patriotique -illustration Léon... - Éliane Daphy /... (Wikimedia Commons, 1910)
Notice iconographique issue de Wikimedia Commons. Titre: Le pioupiou de France - chanson patriotique -illustration Léon Pousthomis- (MédiHAL 1293772). The French Pioupiou: patriotic song | illustration by Léon Pousthomis | lyrics by Ch. Moreau | music by Frédéric Autièro | Marcel Labbé publisher | Minot printing | [interior: rating ML8137 | Minot printing] | blank verso | incipit The sun shines, the road is long | title absent from the Opale-BNF catalog | dating by rating (Devriès & Lesure) 1910.
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie